Reply to Martin Glaberman - Langford, Tom (Labour / Le Travail, 1996)
Responds to Martin Glaberman's critique of his paper, "Strikes and Class Consciousness," published in the Fall 1994 issue. of Labour/Le Travail. Argues that his concept of class consciousness and collective struggle is at the individual, rather than the supraindividual level espoused by Glaberman and György Lukács. Also argues that history does not produce preordained outcomes such as workers' councils, only possibilities of what can be done, which is why he urged Canadian socialists to focus on activist workers who are broadly politicized, non-sectarian, and linked through community networks.
Keywords: Canada; Class consciousness; GLABERMAN, Martin; LABOUR/LE Travail (Book); LANGFORD, Tom; LUKACS, Gyorgy, 1885-1971; STRIKES & lockouts; Socialism